Analisis Sistem Akutansi Pembelian Bahan Baku Food & Beverage Pada Prama Sanur Beach - Ni Nyoman Parmiasih (UNHI Press, 2023)
Hotel Prama Sanur Beach which is engaged in lodging accommodation services often experiences problems in the implementation of its operations, especially in the procurement of raw materials such as wrong orders and invoices that do not match orders. The purpose of this study was to analyze the application of the accounting system for purchasing raw materials for Food & Beverage at Prama Sanur Beach in accordance with the theory. This research uses a comparative descriptive analysis technique. The results of the study revealed that the functions related to the purchasing system were inadequate and not in accordance with the theory because of the dual task of the warehouse function and the receiving function. The documents used in the purchasing system at the Prama Sanur Beach Hotel are not sufficient because there is no Purchase Order Change Letter if there is a change to the contents of the purchase order letter to the supplier officially. The records used in the purchasing system and the network of procedures that make up the purchasing system for food and beverage raw materials at hotels are adequate because they are in accordance with existing theory.